Experimental and numerical investigation on fracture behavior of I-II mixed mode crack for commercially pure Titanium. (August 2018) - Miao, Xin-Ting; Yu, Qin; Zhou, Chang-Yu; Li, Jian; Wang, Yuan-Zhe; He, Xiao-Hua
Graphical abstract: Experimental and numerical investigation on fracture behavior of CTS specimen under I-II mixed mode loading. Highlights: For single edge notched specimen, fracture mode is related with M p . Central cracked specimen is in a tensile-type fracture. For specimen in a tensile-type fracture, ultimate load is almost linear with M p . Difference of constraint resulted from specimen geometry is much greater. Abstract: Both experimental and numerical investigations are performed to study the fracture behaviors of I-II mixed mode crack for commercially pure Titanium (CP-Ti). Three different types of specimens are considered in this paper, including Compact tension shear specimen (CTS specimen), Four point bending specimen (FPB specimen) and Cracked central plate (CCP). Results show that there exist two fracture modes of these specimens, including tensile-type fracture mode and shear-type fracture mode. For single edge notched specimen, the failure mode is determined by plastic mixity parameter M p, and the critical values of M p distinguishing the fracture modes are dependent on the specimen geometry (CTS or FPB specimen). For central cracked plate, specimens are all in a tensile-type fracture mode. Furthermore, specimen in a shear-type fracture mode has a higher loading capability than that in a tensile-type fracture mode. And the loading capability of specimen in tensile-type fracture decreases almost linearly with M p . Finally, constraints of these specimens are analyzed. Discrepancies of constraint between specimens increase with the component of mode I increasing. And the difference of constraint resulted from specimen type is much greater than that from crack length.